DARENDE OVASI VE GÜRÜN ÇEVRESİNİN FİZİKİ COĞRAFYASI - GÜNEK, HALİL (Fırat Üniveristesi, 1995)
The Darende Plain and Giiriin surrounding which constitute our area of investigaiton take place in Upper Euphrates District of Eastern Anatolian Region. Darende Plain and Giiriin (east of Malatya) which has been chosen as the research field cover approximately 2000 km2Our research field which is in the west of East Anatolian Region is diversing in this region and they move apart from each other and is between Southeastern Taurus and Eastern Taurus which are in SW-NE direction and it is vertical to these in the direction of NW-SE within this direction, Kaf Mountain and Cuma Mountain are in the North, Hezanh and Samur Mountains the south,Kepez and Akbabacali Mountains are in the east. White in the above described region is leaning toward Uzunyayla with a swell from the west. Among these steep hills, there are Darende-Balaban, Sugati-Yazikoy Plains and Giiriin Basin which are separated from each other with gradually decreasing swell.The region generally has the characteristic of Eastern Anatolian weather conditions, on the other hand, Inner Anatolia is in the west of the region. As is close to Mediterranean Region and because of it is morphological characteristic, it has got it is own characteristicsThe water in the region is drained by Tohma brook and its branches and this stream flows into Firat. The rivers which are supplied by very rich resources have regular regimein the lower parts of our research field there is brown soil and its surrounding there is chestnut coloured soil. Continuity of this soil is not regular because of Hthosol. In addition, there is bazaltic soil which is developed on bazalts.The vegetation cover of this region consist of natural and antropogen steps. Natural step is found in the lower parts and its height is below than 1200- 1300m. The hight of antropogen step changes from 1200 meters to the peak point.In this doctorate study, The phsical geographich characteristics of Darende Plain and Giiriin surrounding have been examined and the problems of the region from this point of view have been stated and some solutions have been suggested.
Keywords: Coğrafya; Geography